The Biotransformation and Biodecolorization of Methylene Blue by Xenobiotic Bacterium Ralstonia pickettii - Adi Setyo Purnomo; Asranudin Asranudin; Didik Prasetyoko; Yulinar Dwi Nur Azizah (Universitas Gadjah Mada, 2021)
The biotransformation and biodecolorization of methylene blue (MB) dye using the bacterium Ralstonia pickettii was investigated. This experiment was conducted in a nutrient broth (NB) medium after adding MB at 100 mg L–1 concentration. Approximately 98.11% of MB was decolorized after 18 h of incubation. In addition, the metabolic products detected by LC-TOF/MS were Azure A (AA), thionine, leuco-MB, and glucose-MB, which indicated the MB degradation through a reductase that attacked the heterocyclic central chromophore group present in the structure. Moreover, azure A and thionine fragments resulted from the N-demethylase enzyme that attacked the auxochrome group. Thus, this research was assumed to be the first scientific report suggesting the potential to use R. pickettii in the biodecolorization and biotransformation of dye waste, particularly MB.